An underground barrier of locally resonant metamaterial to attenuate surface elastic waves in solids - Feilong Xu; Zhiyu Yang; Xiaodong He; Liang Zhen (AIP Advances, 2020)
The low frequency of seismic waves severely limits the regulation of wave propagation in earthquake protection engineering applications. In recent years, locally resonant metamaterials have been introduced for seismic wave attenuation. A barrier based on locally resonant metamaterials consisting of rows of wells is proposed to reduce the transmission of Rayleigh waves during propagation, achieving earthquake protection. First, comparisons are made between the wells of the metamaterial, empty wells, solid steel wells, and a continuous steel wall. It is evident that locally resonant metamaterials exhibit better performance than that of the other materials. Simulations of the relationships between the attenuation of Rayleigh waves and the depth, number of rows, and working frequency of the wells are presented. With a barrier of ten rows of wells, where the diameter of each well is less than one-twentieth of the wavelength of the Rayleigh wave and the depth of the wells is nearly four-fifths of the wavelength, the maximum attenuation reaches up to 16.2 dB when all the wells share the same working frequency, and the bandwidth is broader, but the maximum value is less when the rows have different working frequencies. Depending on the demand for a higher value or a broader bandwidth of the Rayleigh wave attenuation, this barrier promotes flexible and achievable improvements by adding rows or decentralizing the working frequencies of the wells. The vast potential of seismic wave attenuation from locally resonant metamaterials is anticipated in the future.